Publisher Correction: Single-cell analysis of childhood leukemia reveals a link between developmental states and ribosomal protein expression as a source of intra-individual heterogeneity - Maxime Caron (Nature Portfolio, 2021)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.